Development and polymorphism of microsatellite markers in Neolamarckia cadamba (Roxb.) bosser (kelampayan) using ISSR suppression PCR method - Loi, Phui Seng (Universiti Malaysia Sarawak (UNIMAS), 2012)
Reliable information on the distribution of genetic variation is a crucial point for applicability and efficiency of any breeding, preservation and conservation programmes for forest trees. The emergence of DNA marker technologies provides new tools for rapid genetic analysis, fingerprinting and studying relatedness among cultivars of many forest tree species. A vailability of good numbers of polymerase chain reaction (PCR)compatible DNA markers which is heritably co-dominant and multiallelic has become a priority due to the genetic complexity of breeder's populations and high levels of heterozygosity in individual genotypes. Simple sequence repeats (SSRs) or microsatellites, are tandemly repeated motifs of 1-6 nuc1eotides found in all prokaryotic and eukaryotic genomes. The uniqueness and value of micro satellites arises from their multiallelic nature, codominant transmission, relative abundance and extensive genome coverage. Because of these attributes, microsatellites are currently the excellent markers of choice for comparative genetic and genomic analysis, high-throughput genotyping and studies of gene flow in forest trees. Neolamarckia cadamba (Roxb.) Bosser or locally known as Kelampayan, belongs to the Rubiaceae, was chosen in the present study due to its high commercial value and fast growing ability. Although N cadamba becomes one of the most frequently planted trees in the tropics, but genetic information about this species is limited and none of the DNA markers has been developed from N cadamba compared to other economically important tropical trees. In the present study, 15 SSR markers specific for N cadamba were developed using inter-simple sequence repeat (ISSR) suppression PCR method, a method which is relatively simple and rapid without enrichment steps. Considerable allelic amplifications were obtained for all SSR markers across the tested genotypes whereby 66 alleles were detected with an average of 4 per locus. Most of the detected loci analyzed showed high polymorphism as indicated by their PIC value which was above 0.5. The most polymorphic loci were: ACll (PIC=0.849), ACl2 (PIC=0.722) and AGOl (PIC=0.712). Besides, cross-speCies transferability of micro satellites was also confirmed in this study and the newly developed SSR markers showed good cross species amplification efficiency. These SSR markers represent a potent tool for genetic diversity study, estimate pollen contamination in seed orchards, germplasm identification and to assist with the construction of genetic linkage map for N cadamba. The derived SSR-based map later will be an important prerequisite for marker-assisted selection (MAS) to increase the efficiency of N cadamba breeding.